Effects of cumin extract on oxLDL, paraoxanase 1 activity, FBS, total cholesterol, triglycerides, HDL-C, LDL-C, Apo A1, and Apo B in in the patients with hypercholesterolemia - Samani, Keihan Ghatreh; Farrokhi, Effat (International Journal of Health Sciences, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–> Objectives: Paraoxanase 1 (PON1) plays a protective role against the oxidative modification of plasma lipoproteins and hydrolyzes lipid peroxides in human atherosclerotic lesions. Cumin is the dried seed of the herb Cuminumcyminum that is known as Zeera in Iran. Cumin seeds contain flavonoids which are now generally recognized to have antioxidant activity and improve the antioxidant system. So, they possibly modify PON1 activity and oxidized low density lipoprotein (oxLDL) level. The present study was aimed to evaluate the effects of cumin extract supplementation on oxLDL, paraoxanase 1 activity, FBS, total cholesterol, triglycerides, High density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), apolipoprotein A1 (<span style="font-size: 8.0pt; font-family: ’Arial’,’sans-serif’; mso-ascii-theme-font: minor-bidi; mso-fareast-font-family: ’Times New Roman’; mso-hansi-theme-font: minor-bidi; mso-bidi-theme-font: minor-bidi; mso-font-kerning: 18.0pt;">Apo A1), and apolipoprotein B<span style="font-size: 8.0pt; font-family: ’Arial’,’sans-serif’; mso-ascii-theme-font: minor-bidi; mso-fareast-font-family: ’Times New Roman’; mso-hansi-theme-font: minor-bidi; mso-bidi-theme-font: minor-bidi; mso-font-kerning: 18.0pt;"> (Apo B)in the patients with hypercholesterolemia. Methodology: A fasting venous blood sample was obtained from the voluntary persons before and 45Â±3 days after taking cumin. Glucose, total cholesterol, and triglycerides were assayed using standard enzymatic procedures. HDL-Cand LDL-C were measured by direct method and ApoA1 and ApoB levels by immunoturbidimeteric methods. The levels of arylesterase and paraoxanase activities in the samples were measured by photometry methods and oxLDL by enzyme-linked immunosorbent assay (ELISA) method. 3 to 5 drops of cumin extract were added to the patient’s diet three times a day based on manufacturerâ€™s instruction for 45Â±3 days. The biochemical parameters were compared before and after taking cumin. Data were analyzed using paired Studentâ€™s t-test in SPSS statistical software (version 11.5). Results: The results demonstrated that there was a significant decrease in the level of oxLDL after receiving cumin. Paraoxonase and arylesterase activities increased in serum after taking cumin extract.Â Conclusion: Based on the results, cumin reduces oxLDL level and increases both paraoxonase and arylesterase activity. Keywords: Cuminum, Oxidized low density lipoprotein, High density lipoprotein cholesterol, Paraoxanase 1, Arylesterase, Apolipoprotein A1, Apolipoprotein B Abbreviations: PON1: Paraoxanase 1, oxLDL: Oxidized Low Density Lipoprotein, HDL-C: High Density Lipoprotein Cholesterol, ELISA: Enzyme-Linked Immunosorbent Assay, ApoA1: Apolipoprotein A1, ApoB: Apolipoprotein B, MDA: Malondialdehyde, VLDL: Very Low Density Lipoprotein, IDL: Intermediate Density Lipoprotein, LDL-C: Low Density Lipoprotein Cholesterol, TC: Total Cholesterol, TG: Triglycerides, FBS: Fasting Blood Sugar, BMI: Body Mass Index <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>